Tea polyphenols improve glucose metabolism in ceruloplasmin knockout mice via decreasing hepatic iron deposition - Lei Ying; Liu Yan; Zhou Huimin; Li Min; Zhang Xiaojuan; Wang Zhanjian; Zhou Yaru (CyTA - Journal of Food, 2022)
The present study aimed to investigate the role of tea polyphenols (TP) playing in glucose metabolism in male ceruloplasmin knockout mice (CP−/−), an iron-overloaded model. Compared to wild-type CP+/+ mice, CP−/− mice exhibited hyperglycemia, insulin resistance and excess iron deposition in liver tissue. Increased hepatic oxidative stress (P＜0.05), apoptosis, and reduced gene expression of insulin receptor substrate 2 (IRS2) and glucose transporter 2 (GLUT2) were found in CP−/− mice (P＜0.05). TP treatment may ameliorate hepatic iron overload, oxidative stress and apoptosis, improve insulin sensitivity by upregulating IRS2 and GLUT2 expressions. TP administration could improve glucose homeostasis in CP−/− mice by alleviating hepatic iron-overload, oxidative stress, hepatocyte apoptosis, and restoring insulin signaling pathway.